Long noncoding RNA UCA1 promotes chondrogenic differentiation of human bone marrow mesenchymal stem cells via miRNA-145-5p/SMAD5 and miRNA-124-3p/SMAD4 axis - Shu, Tao; He, Lei; Wang, Xuan; Pang, Mao; Yang, Bu; Feng, Feng; Wu, Zizhao; Liu, Chang; Zhang, Shufan; Liu, Bin; Wang, Qiyou; Rong, Limin (Biochemical and biophysical research communications, 2019)
Long noncoding RNA (lncRNAs) UCA1 has been known to be critical for the chondrogenic differentiation of marrow mesenchymal stem cells (MSCs). In this study, we explore the effects and mechanisms of UCA1 on the promotion of chondrogenesis of MSCs. During the processes of chondrogenic differentiation of MSCs, UCA1, miRNA-145-5p or miRNA-124-3p was overexpressed into MSCs. UCA1 substantially improved chondrogenesis of MSCs. Furthermore, UCA1 obviously down-regulated the expression of miRNA-145-5p and miRNA-124-3p, which attenuated the chondrogenic differentiation of MSCs. In addition, UCA1 significantly stimulated TGF-β pathway member SMAD5 and SMAD4, which is targeted by miRNA-145-5p and miRNA-124-3p. Collectively, these outcomes suggest that UCA1 enhances chondrogenic differentiation of MSCs via the miRNA-145-5p/SMAD5 and miRNA-124-3p/SMAD4 axis. •UCA1 promoted the chondrogenic differentiation of MSCs.•UCA1 down-regulated miRNA-145-5p/miRNA-124-3p during this process.•miRNA-145-5p targeted SMAD5 and miRNA-124-3p targeted SMAD4.